Analisis Ide Pemikiran John Locke : Trias Politica dan HAM - Haq, Nanda Zadina Khansa’ (Maliki Interdisciplinary Journal, 2025)
Analysis of John Locke’s ideas about Trias Politica and Human Rights (HAM) is the main focus of this article. Locke, a 17th-century political philosopher, made important contributions to the theory of democratic government and individual rights. The Trias Politica concept he promoted proposed a division of power between the executive, legislative and judiciary to prevent abuse of power. An in-depth analysis of this aspect discusses how Locke views the importance of a balance of power in order to protect individual freedom. Apart from that, Locke also developed ideas about human rights. An in-depth analysis of his perspective on individual rights such as the rights to life, liberty and property is the focus of the writing. Locke saw that these rights were natural and could not be taken away by the government. This understanding leads to a discussion of how Locke constructs the basis of arguments to avoid violations of human rights by the government. Throughout this analysis, emphasis is placed on the relevance of Locke’s thought to the contemporary context. The extent to which the principles of Trias Politica and the human rights it promotes can be implemented in the context of modern society and the state is an important consideration. The conclusion underscores the importance of Locke’s thought in forming the conceptual basis for democratic government and the protection of individual rights in the development of today’s political system.